From Topophobia to Topophilia: The Routledge Handbook of Literature and Space (KULT_online, 2018)
The Routledge Handbook of Literature and Space provides a comprehensive critical overview of the latest advancements in the arena of spatial literary studies. Its primary questions move along the avenues opened up for literary criticism by the ‘spatial turn’ in cultural studies and the humanities in general. The investigations illuminate key concerns regarding the reciprocal relationships between spatiality and the human senses, their production of spatial and social relations, as well as an interpretation of space as a fluid dimension constantly in a state of becoming. The contributions present thoroughgoing analyses of a wide array of literary texts from diverse historical and geographical settings, and frequently evidence the profound impact that recent phenomenological and New Materialist bents have exerted on literary study. Expansive in scope and content, yet incisive and approachable, the volume should find both novices and experts, from the full range of disciplines that it engages with, among its reading public.